Meninjau Penerapan Kaidah Idza Tsaqata Al Ashlu Tsaqata Al Far’u Pada Bisnis Dan Ekonomi - Siswanto (Sekolah Tinggi Agama Islam Al-Hikmah 2, 2023)
In solving the contemporary problems, The Legal Maxims of Islamic Jurisprudence has an important position for that or providing alternative solutions to various problems that arise, especially in this modern era. The devinitive legal answers to current modern problems are often not found in the Al-Qur'an and As-Sunnah and even in the classic books that are discussed by by earlier scholars. Therefore, the principles of fiqh (Qawaidul Fiqhiyah) have been formulated by earlier islamic scholars of fiqh, then have become an important medium for doing ijtihad in the realm of formulating laws/istimbatil ahkam in these issues. One of them is using the principle of idza tsaqata al ashlu tsaqata al far'u. Therefore, through this short paper, the author tries to explain the meaning and application of this method in the operational activities of muamalah business and especially in the world of financing transactions in Islamic banking